2006
DOI: 10.1210/en.2005-1565
|View full text |Cite
|
Sign up to set email alerts
|

Starting the Zebrafish Pineal Circadian Clock with a Single Photic Transition

Abstract: The issue of what starts the circadian clock ticking was addressed by studying the developmental appearance of the daily rhythm in the expression of two genes in the zebrafish pineal gland that are part of the circadian clock system. One encodes the photopigment exorhodopsin and the other the melatonin synthesizing enzyme arylalkylamine N-acetyltransferase (AANAT2). Significant daily rhythms in AANAT2 mRNA abundance were detectable for several days after fertilization in animals maintained in a normal or rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 26 publications
2
49
2
4
Order By: Relevance
“…The pineal opsin protein Exorh is expressed in pineal photoreceptors from early embryogenesis to adulthood and is thus an excellent candidate to be mediating these light responses [5,38,60]. Consistent with this, the action spectrum of acute melatonin suppression in isolated adult pineal organs suggests that Exorh is one of several opsins involved in this process [65].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…The pineal opsin protein Exorh is expressed in pineal photoreceptors from early embryogenesis to adulthood and is thus an excellent candidate to be mediating these light responses [5,38,60]. Consistent with this, the action spectrum of acute melatonin suppression in isolated adult pineal organs suggests that Exorh is one of several opsins involved in this process [65].…”
Section: Introductionmentioning
confidence: 70%
“…Vuilleumier and colleagues recently reported that exorh is expressed with a daily rhythm, with higher expression during the dark phase of the circadian cycle [60]. However, they found that the day/night differences in expression were not statistically significant [60].…”
Section: Results Exorh Transcription Is Rhythmicmentioning
confidence: 98%
See 3 more Smart Citations